Effect of L/N-type Calcium Channel Blocker (Cilnidipine) on Oxidative Stress in Nitric Oxide-Deficient Hypertensive Rats - Gouher Banu Shaikh; Surekha Hippargi; Dewan S A. Majid; M S Biradar; Kusal K Das (Wolters Kluwer Medknow Publications, 2020)
Background: The sympathetic nervous system plays a major role in the renal function through the vasoactive system and the Renin-Angiotensin-Aldosterone System. Even though interest in the renal protective effects of sympathetic blocker has been increased, there are not much data to clarify this efficiency in nitric oxide deficient hypertensive rats. Aim and Objectives: To find out the effect of cilnidipine, L/N-type calcium channel blocker on oxidative stress of kidney in nitric oxide synthase (NOS) inhibited experimental hypertensive rats. Material and Methods: Male Albino Wistar rats (n-24) were randomly allocated into four groups: group 1, control received vehicle; group 2, received Cilnidipine; group 3, received NG-nitro-L-arginine methyl ester hydrochloride (L-NAME); group 4, received L-NAME &Cilnidipine; All drugs are given orally for 4 weeks. Blood pressure was measured before and after the intervention and twice during intervention for all the rats. On the 29th day, blood was collected and animals were sacrificed and kidneys were collected. Serum and kidney tissue malondialdehyde (MDA) levels are estimated. Results: The results demonstrate that there is a significant increase in Mean Arterial Pressure (MAP) in L-NAME treated rats compared to the control group. Treatment with cilnidipine significantly decreases the MAP in group 4 rats. We also demonstrated the significantly elevated serum and kidney tissue MDA levels in L-NAME treated rat. Treatment with Cilnidipine reduced serum and kidney tissue MDA levels in group 4 rats compared to group 3 rats. Conclusion: The results demonstrate that cilnidipine has suppressive effects against progressive renal injury as evidenced by decreased oxidative stress indicator MDA levels in NO deficient hypertensive rats. This effect is explained by the L/N type calcium channel inhibition of cilnidipine, the L-type calcium channel blocking action lowers blood pressure and N-type calcium channel blocking action leads to suppression of the sympathetic nerve activity and renin-angiotensin-aldosterone system.